Special report of the National Advisory Council on Increase in Resources of the International Development Association. Letter from the Secretary of the Treasury transmitting a special report... concerning a proposed increase in the resources of the International Development Association. September 16, 1963. -- Referred to the Committee on Banking and Currency and ordered to be printed. - United States; United States; United States (Washington, DC. : United States of America Government Printing Office, 1963)
Special report of the National Advisory Council on increase in resources of the International Development Association.
Table of contents, p. V.
Appendices, p. 9.
rua 13/12/16
Ref.
Keywords: Bank loans; Economic development; Foreign aid; International agencies; International cooperation; International economic relations